2018
DOI: 10.4149/neo_2018_170112n26
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine (TMPZ) triggers S-phase arrest and mitochondria- dependent apoptosis in lung cancer cells

Abstract: Tetramethylpyrazine (TMPZ) is one of the active compounds extracted from the traditional Chinese herb Chuanxiong. Several studies have shown its anti-cancer properties. However, its functions in lung cancer and the underlying cellular mechanisms are relatively unknown. Our present study aimed to investigate the effects of TMPZ on A549 and 95D cells. The MTT assay showed that TMPZ decreased cell viability in a dose- and time-dependent manner. The results of the colony formation assay indicated that TMPZ strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…It indicated that the inhibitory effect of ligustrazine on cell proliferation was a positive correlation to the concentration and treatment time. The findings demonstrated that ligustrazine had significant anti-tumor activity, which was consistent with previous studies (21)(22)(23).…”
Section: Discussionsupporting
confidence: 92%
“…It indicated that the inhibitory effect of ligustrazine on cell proliferation was a positive correlation to the concentration and treatment time. The findings demonstrated that ligustrazine had significant anti-tumor activity, which was consistent with previous studies (21)(22)(23).…”
Section: Discussionsupporting
confidence: 92%
“…TMP has shown antitumor effects on various tumor types ( Figure 2 ), including brain glioma ( Cai et al, 2014 ), breast ( Fan et al, 2021 ), prostate ( Zhou et al, 2020 ), and lung cancers ( Huang et al, 2018 ). Tumor growth can be reversed by applying different concentrations of TMP to tumor cells.…”
Section: Antitumor Mechanism Underlying the Effects Of Tetramethylpyrazine In Multiple Organsmentioning
confidence: 99%
“…The underlying mechanisms involve inhibition of platelet aggregation, suppression of apoptosis, and scavenging peroxyl radicals, superoxide, and hydroxyl radicals[ 8 ]. Recent studies have demonstrated that TMP has potent inhibitory effects on a number of types of tumors, such as lung, breast, ovarian carcinoma, gastric carcinoma, osteosarcoma, leukemia, and hepatocellular carcinoma, through affecting the proliferation and apoptosis of tumor cells[ 9 - 13 ]. However, the effects of TMP on colon cancer have not been investigated.…”
Section: Introductionmentioning
confidence: 99%